UJI AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT DAN DAGING BUAH NAGA MERAH (Hylocereus polyrhizus) DANPENENTUAN PARAMETER NON SPESIFIK - Aliya, Nuska; Riyanta, Aldi Budi; Muldiyana, Tya (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Red dragon fruit is one of the fruits that is often consumed by the Indonesian people because it is rich in properties and benefits. In addition to the fruit, red dragon fruit skin can also be used as a natural colorant in food and cosmetics. One of the beneficial compounds contained in the skin and flesh of red dragon fruit is antioxidant. This study aims to determine the differences in antioxidant activity and non-specific parameters of red dragon fruit skin and flesh extracts. The samples used are skin and flesh of red dragon fruit, in addition to comparing fresh samples and dried simplisia of each skin and flesh, dried simplisia samples from each skin and flesh. Method extraction method used in this study is reflux method with 70% ethanol solvent. Antioxidant activity was determined by IC50 value. From the IC50 calculation, it was found that red dragon fruit peel extract with fresh samples and dry simplisia included strong antioxidants while antioxidants in red dragon fruit flesh were lower with weak antioxidant activity. The difference in the use of simplisia also affects the antioxidant activity of the extract, extracts using dry simplisia have higher antioxidant activity than extracts using fresh samples. While in the test of non-specific parameters of the extract there is no significant effect.